2011
DOI: 10.1002/ana.22155
|View full text |Cite
|
Sign up to set email alerts
|

The COMT Val158Met polymorphism affects the response to entacapone in Parkinson's disease: A randomized crossover clinical trial

Abstract: The COMT(HH) genotype in PD patients enhances the effect of entacapone on the pharmacodynamics and pharmacokinetics of levodopa. The response to entacapone after repeated administrations and in heterozygous patients remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 22 publications
(34 reference statements)
5
51
0
3
Order By: Relevance
“…P-value: regression analysis of the COMTgenotype effect on binding potential (BP) in the total striatum, putamen, and caudate nucleus, adjusted to UPDRS part III, age and gender. in PD patients [17,18]. A PET study recently confirmed that the Val158Met polymorphism also modifies dopamine turnover in the prefrontal cortex in PD patients [19].…”
Section: Discussionmentioning
confidence: 88%
“…P-value: regression analysis of the COMTgenotype effect on binding potential (BP) in the total striatum, putamen, and caudate nucleus, adjusted to UPDRS part III, age and gender. in PD patients [17,18]. A PET study recently confirmed that the Val158Met polymorphism also modifies dopamine turnover in the prefrontal cortex in PD patients [19].…”
Section: Discussionmentioning
confidence: 88%
“…9 10 Other studies showed that the genotype directly affects executive function in early stage PD; Val/Val patients have less frontoparietal activation on fMRI 11 and better performance on executive tasks. 8 11 A pharmacogenetic study showed that the COMT polymorphism determines the acute response to entacapone, 31 although the motor response to levodopa alone was not modified by the COMT polymorphism. 31 32 These results collectively show that the COMT polymorphism modifies the PD phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmakogenetische Studien kommen zu dem Ergebnis, dass es bei medizierten Parkinson-Patienten einen Zusammenhang gibt zwischen einem Polymorphismus im Dopamin-D2-RezeptorGen (C-Allel des TaqIA Polymorphismus 10.5. kb 3') und spät einsetzenden Psychosen [ 16 ] . Eine randomisierte Cross-over-Studie zeigte, dass der COMT-Val158Met-Polymorphismus, der die COMT-Aktivität moduliert, einen Einfl uss auf die Wirkung von Entacapon hat [ 19 ] : Parkinson-Patienten mit dem COMT(HH)-Allel hatten im Vergleich zu Patienten mit dem COMT(LL)-Allel nach einer akuten L-DOPA-Applikation eine höhere On-Zeit (39 vs. 9 min) und eine erhöhte Bioverfügbarkeit von L-DOPA (AUC 62 vs. 34 %).…”
Section: Genetische Veränderungen An Molekularen Zielstrukturenunclassified